2021
DOI: 10.1007/s10826-021-02129-5
|View full text |Cite
|
Sign up to set email alerts
|

Direct and Indirect Associations between Family Residential Mobility, Parent Functioning, and Adolescent Behavioral Health

Abstract: Residential mobility and caregiver social support are two key factors influencing adolescents’ and their caregivers’ health status. However, few studies have examined whether these factors vary across developmental periods. The present study therefore adopted a life course perspective to investigate the longitudinal effects of residential mobility and caregiver social support on a range of individual health outcomes (i.e., caregiver depression, adolescent internalizing problems, and adolescent externalizing pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 62 publications
(86 reference statements)
1
0
0
Order By: Relevance
“…Similar with previous studies showing that higher levels of screen time, especially for video games and television viewing are associated with grater social behavioral problems among youth (Carson et al, 2016;Guerrero et al, 2019), we also found a similar significant relationship for engagement into delinquent behavior. Experiencing environmental changes (e.g., moving to another city) is significantly associated with depression and both externalizing problems, supporting the previous results showing that residential mobility is a disrupting event for adolescents, thus triggering psychological and behavioral problems (Anderson & Leventhal, 2017;Du & Kim, 2021).…”
Section: Discussionsupporting
confidence: 83%
“…Similar with previous studies showing that higher levels of screen time, especially for video games and television viewing are associated with grater social behavioral problems among youth (Carson et al, 2016;Guerrero et al, 2019), we also found a similar significant relationship for engagement into delinquent behavior. Experiencing environmental changes (e.g., moving to another city) is significantly associated with depression and both externalizing problems, supporting the previous results showing that residential mobility is a disrupting event for adolescents, thus triggering psychological and behavioral problems (Anderson & Leventhal, 2017;Du & Kim, 2021).…”
Section: Discussionsupporting
confidence: 83%